Clinical trial of new rice - Soil absorbable bone plug - Sittiporn Punyanitya (2020)
© 2019 Elsevier Ltd. All rights reserved. Rice-soil is a novel biomedical product intended for tamponading the bleeding from bone surfaces. Previous research, we have made it from blending of rice starch, glycerin, KOH, stearic acid and ethanol. In clinical trial, rice-soils will be used in 60 volunteered patients, 15 orthopedics and 45 neurosurgicals, then all patients were followed for as long as 6 months. The satisfactory of material is more than 95% grading from operative surgeons and nurses. No ill effects or complications from the long term follow-up. Rice soil is safe, clinically effective and economically acceptable. It should be an alternative choice for general hospital.